Unemployment Hysteresis, Wage Determination, and Labor Market Flexibility : The Case of Belgium. (IMF Working Papers; Working Paper ;, 1994)
This paper examines the potential contribution of unemployment hysteresis theories to the understanding of the Belgian labor market. It estimates models of wage determination using aggregate and firm-level panel data. Two main conclusions emerge: (i) the long-term unemployed do not exert a negative impact on wages; and (ii) there is some evidence that the incumbent workers, the 'insiders,' exercise market power in wage determination, taking greater account of their own interests than those of the unemployed 'outsiders.' In addition, it is argued that the automatic indexation of wages to prices in Belgium can cause a downward rigidity in real wages, given the multi-tier real wage bargaining process. Recent initiatives, including the introduction of a competitiveness norm for indexation, and labor market programs aimed at the long-term unemployed and the young, such as the plan d'accompagnement and the plan d'embauche des jeunes, are appropriate in view of the existence of insider power in wage determination.